2010
DOI: 10.1111/j.1439-0485.2009.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐water Corallium rubrum (L., 1758) from the Mediterranean Sea: preliminary genetic characterisation

Abstract: The precious red coral Corallium rubrum (L., 1758) lives in the Mediterranean Sea and adjacent Eastern Atlantic Ocean on subtidal hard substrates. Corallium rubrum is a long‐lived gorgonian coral that has been commercially harvested since ancient times for its red axial calcitic skeleton and which, at present, is thought to be in decline because of overexploitation. The depth distribution of C. rubrum is known to range from c. 15 to 300 m. Recently, live red coral colonies have been observed in the Strait of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 48 publications
2
64
0
Order By: Relevance
“…rubrum is a slow growing, long lived, gorgonian coral endemic of the Mediterranean Sea. This coral is commonly found on hard substrates, on steep walls and overhangs, below 10 m depth (Rossi et al, 2008) and down to 800 m (Costantini et al, 2010), with the typical range being ∼25-60 m (Rossi et al, 2008). It is associated with the coralligenous communities (Tsounis et al, 2010), a collective term referring to complex biogenic structures made by the outgrowth of encrusting calcareous algae on hard substrate in the mesophotic zone.…”
Section: Case Study 1 Hazard Layer For the Thermal Threshold Of 25 • Cmentioning
confidence: 99%
“…rubrum is a slow growing, long lived, gorgonian coral endemic of the Mediterranean Sea. This coral is commonly found on hard substrates, on steep walls and overhangs, below 10 m depth (Rossi et al, 2008) and down to 800 m (Costantini et al, 2010), with the typical range being ∼25-60 m (Rossi et al, 2008). It is associated with the coralligenous communities (Tsounis et al, 2010), a collective term referring to complex biogenic structures made by the outgrowth of encrusting calcareous algae on hard substrate in the mesophotic zone.…”
Section: Case Study 1 Hazard Layer For the Thermal Threshold Of 25 • Cmentioning
confidence: 99%
“…By and large, the most relevant actors of such aphotic communities are cnidarians and sponges associated with poorly sampled hard bottoms at depths exceeding 200 m. This is primarily the case for the so-called white coral communities documented at bathyal depths in the Strait of Sicily, southern Adriatic, Ionian, Ligurian, Marmara, northwestern Mediterranean and Alboran seas (Tursi et al 2004;Taviani et al 2005aTaviani et al , 2005bTaviani et al , 2011aFreiwald et al 2009;Mastrototaro et al 2010;Vertino et al 2010;Gori et al 2013;Angeletti et al 2014;Fabri et al 2014), the sponge-dominated habitats in the Tyrrhenian, Ionian and Adriatic seas (Bo et al 2012;Calcinai et al 2013), and antipatharian-gorgonacean communities in the Tyrrhenian, Ionian and Adriatic seas and in the Strait of Sicily (Costantini et al 2010;Taviani et al 2010;Bo et al 2011;Angeletti et al 2014;Deidun et al 2014). From this ecological perspective, the Malta Escarpment in the central Mediterranean happens to be one of the least explored in European waters.…”
Section: Introductionmentioning
confidence: 99%
“…Often, it coexists with a rich fauna of benthic invertebrates, such as other anthozoan species (gorgonians and hard corals), sponges, as well as calcareous algae (e.g. Ballesteros 2006;Costantini et al 2010). Research has shown that the Mediterranean Red Coral can live more than 100 years and its slow recruitment and growth rate (colonies grow in diameter about 0.25 mm per year, with a higher growth in the early stages of life) hightlight the slow recovery times of disturbed populations (Marschal et al 2004).…”
Section: Following the Gfcm Recommendation 35/2011mentioning
confidence: 99%